2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594060
|View full text |Cite
|
Sign up to set email alerts
|

PiRat: An Autonomous Framework for Studying Social Behaviour in Rats and Robots

Abstract: The use of robots, as a social stimulus, provides several advantages over using another animal. In particular, for rat-robot studies, robots can produce social behaviour that is reproducible across trials. In the current work, we outline a framework for rat-robot interaction studies, that consists of a novel rat-sized robot (PiRat), models of robotic behavior, and a position tracking system for both robot and rat. We present the design of the framework, including constraints on autonomy, latency, and control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Using human operated robots will be sufficient to make progress in the areas listed above, but behaviors will ultimately need to be fully automated, so that generalizable experiments can be run by different researchers across institutions. Automated chasing of an individual by a robot is already possible (Heath et al, 2018), but a fuller suite of robot postures/responses requires subtler timing and perception, almost certainly requiring advanced machine learning for visual classification of animal behaviors, which is an already an active topic of research (Nilsson et al, 2020), but not yet integrated into robot development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using human operated robots will be sufficient to make progress in the areas listed above, but behaviors will ultimately need to be fully automated, so that generalizable experiments can be run by different researchers across institutions. Automated chasing of an individual by a robot is already possible (Heath et al, 2018), but a fuller suite of robot postures/responses requires subtler timing and perception, almost certainly requiring advanced machine learning for visual classification of animal behaviors, which is an already an active topic of research (Nilsson et al, 2020), but not yet integrated into robot development.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 is limited to rodent-mimicking hardware designed with animal interaction in mind-several other works exist exploring rodent interaction with off the shelf robots (e.g., Del Angel Ortiz et al, 2016), using rat-biomimicry to develop novel hardware (e.g., Pearson et al, 2007), implementing rat-like behaviors to test neuromechanical hypotheses in-silico (e.g., Fend et al, 2004), or testing virtual robots (Merel et al, 2019). While many robots take the approach of attempting to replicate as directly as possible the kinematics of rat movement, currently the robots most widely tested in animal interactions use simplified geometry and rely on wheels (Shi et al, 2011(Shi et al, , 2012(Shi et al, , 2015Wiles et al, 2012;Heath et al, 2018;Yamada et al, 2021). This allows them to move at similar speeds to rats over engineered/flat surfaces (∼1 m/s), but comes with the cost of being unable to move over more complicated terrain, or to replicate rat body postures (e.g., rearing Yuanzhong et al, 2022).…”
Section: State Of the Art In Biohybrid Rodent Studiesmentioning
confidence: 99%
“…However, WoZ is a necessary step in the development of autonomous systems allowing for a diverse collection of movement dynamics that autonomous robots currently lack the complexity and sensitivity to exhibit. Follow up studies will be performed using autonomous robotic systems, such as PiRat ( Heath et al, 2018 ). Autonomous robots allow for the manipulation of dynamics or functions that can be systematically manipulated according to model-based reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to examining behaviors related to novelty and fear, studies have also been performed examining the similarity between rodent social behaviors and behaviors toward a robot. Rats have been shown to behave similarly toward mobile robots as they do to rats, exhibiting behaviors such as: approaching, avoiding, sniffing, and following ( Wiles et al, 2012 ; del Angel Ortiz et al, 2016 ; Heath et al, 2018 ). The analysis showed that the rats demonstrated similar relative orientation formations when interacting with another rat or moving robot.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to examining behaviors related to novelty and fear, studies have also been performed examining the similarity between rodent social behaviors and behaviors toward a robot. Rats have been shown to behave similarly towards mobile robots as they do to rats, exhibiting behaviors such as: approaching, avoiding, sniffing, and following (del Angel Ortiz et al, 2016;Wiles et al, 2012;Heath et al, 2018). The analysis showed that the rats demonstrated similar relative orientation formations when interacting with another rat or moving robot.…”
Section: Introductionmentioning
confidence: 99%